The European energy scene : papers presented at the Tenth Consultative Council of the Watt Committee on Energy, London, 21 May 1981.: papers presented at the Tenth Consultative Council of the Watt Committee on Energy, London, 21 May 1981. ([2014?]) - Unknown
No abstract available